Peningkatan Bobot Karkas Burung Puyu Bet Dina melalui Penambahan Tepung Daun Pandan (Pandanus Amaryllifolius) dalam Pakan - Datau, Fahria; Laya, nibras K; Dako, Safriyanto (Gorontalo Journal of Equatorial Animals, 2024)
This study aims to determine the Effect of Pandan Leaf Flour (Pandanus amaryllifolius) on Carcass Weight and Carcass Parts of Female Quail. This study was conducted from September to December 2023 at the Animal Husbandry Technology Laboratory, Faculty of Agriculture, Gorontalo State University. The study used 200 female quail. The cage used a battery model of 15 plots with a size of 50 cm x 50 cm x 40 cm. The feed given consisted of BR-21 quail feed and pandan leaf flour. The research method used was a Completely Randomized Design (CRD). The treatment of pandan leaf flour in the feed was 0%, 4%, 6%, 8% and 10%, respectively. The parameters measured included carcass weight and carcass part weight. The results showed that giving pandan leaf flour up to 10% did not have a significant effect on carcass weight and carcass parts of female quail.Keywords: Quail; body weight; carcass; non carcass